Research progress in endothelial cell injury and repair - Huang, Yongpan; Song, Chong; He, Jianbin; Li, Min (Frontiers in Pharmacology, 2022)
Endothelial cells, which are important metabolic and endocrine cells, play an important role in regulating vascular function. The occurrence and development of various cardiovascular and cerebrovascular diseases are associated with endothelial dysfunction. However, the underlying mechanism of vascular endothelial injury is not fully understood. It has been reported that the mechanism of endothelial injury mainly involves inflammation and oxidative stress. Moreover, endothelial progenitor cells are regarded as important contributors in repairing damaged endothelium. Multiple interventions (including chemical drugs and traditional Chinese medicines) exert endothelial protection by decreasing the release of inducing factors, suppressing inflammation and oxidative stress, and preventing endothelial cell senescence.